(untitled) (The International Journal for Scientific Research, 2026)
The United States has always considered the Middle East a region of vital interests, viewing it as a crucial geopolitical area that fulfills its economic, security, and even military needs. American projects in the region are implemented to implement its plans and strategies aimed at securing energy resources, protecting its economic interests, and maintaining Israel’s security. Consequently, the United States has continued to impose its policies on its Gulf allies within a framework of appeasement, or rather, a policy of dependency and guardianship. This includes normalization with the Zionist entity, in which America has achieved considerable success, particularly after the 2020 Abraham Accords, known as the "Deal of the Century" during Trump’s first term. Driven by Joe Biden’s desire to replicate the achievements of previous American presidents, he initiated mediation between Saudi Arabia and the Zionist entity to begin normalization negotiations. This is part of his own project, which will enhance his standing within the United States, given the Kingdom’s significant influence in the Middle East and the wider Muslim world. Furthermore, normalization will have significant repercussions for the region, both positive and negative, especially in light of the economic rise of China, Russia, and even Iran in the region. This posed a clear threat to the United States’ position and dominance in the Middle East.